(untitled) (Journal of Atomic and Molecular Sciences, 2018)
In this present work, the sensing mechanism of a novel fluoride chemosensor 2,2':6',2''-terpyridine (abbreviated as “2” according to previous experiment) has been investigated based on density functional theory (DFT) and time-dependent DFT (TDDFT) methods. The theoretical electronic spectra (vertical excitation energies and fluorescence peak) reproduced previous experimental results [RSC Adv. 2014, 4, 4041.], which confirms the rationality of our theoretical level used in this work. The constructed potential energy curve suggest that the non-barrier process could be responsible for the rapid response to fluoride anion. Analyses about binding energies demonstrate that only fluoride anion could be detected for 2 chemosensor in acetonitrile solvent. Comparing with other anions, we confirm the uniqueness of fluoride anion for 2 sensor. In view of the excitation process, the strong intramolecular charge transfer (ICT) process of S_0→ S_1 transition explain the redshift of absorption peak for 2 sensor with the addition of fluoride anion. This work not only presents a straightforward sensing mechanism of fluoride anion for 2 chemosensor, but also plays important roles in synthesizing and designing fluorescent sensors in future.